2014
DOI: 10.1007/s40477-014-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of articular disc displacement of temporomandibular joint with ultrasound

Abstract: Purpose To assess pattern of articular disc displacement in patients with internal derangement (ID) of temporomandibular joint (TMJ) with ultrasound. Materials and methods Prospective study was conducted upon 40 TMJ of 20 patients (3 male, 17 female with mean age of 26.1 years) with ID of TMJ. They underwent highresolution ultrasound and MR imaging of TMJ. The MR images were used as the gold standard for calculating sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…MR imaging has a role in the assessment of knee joint but it is expensive [7][8][9][10]. Ultrasound is becoming more popular in the evaluation of different musculoskeletal abnormalities such as different rheumatic disease, soft tissue lesions, and joints [10][11][12][13][14]. Few studies discuss the role of ultrasound in knee joint [15][16][17] as well as ultrasound findings in patients with knee osteoarthritis [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…MR imaging has a role in the assessment of knee joint but it is expensive [7][8][9][10]. Ultrasound is becoming more popular in the evaluation of different musculoskeletal abnormalities such as different rheumatic disease, soft tissue lesions, and joints [10][11][12][13][14]. Few studies discuss the role of ultrasound in knee joint [15][16][17] as well as ultrasound findings in patients with knee osteoarthritis [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…For the reference standard domain, we consider the risk of bias high in one study [35], because the reference standard findings were interpreted without blinding of the index test results. The risk of bias in another four studies was considered unclear [24, 29, 32, 33], because we were unable to confirm whether the reference standard results were interpreted in a blinded manner of the index test findings. In the flow and timing domain, we considered the risk of bias high in three studies [23, 28, 35], because not all the patients included were in the final analysis in these studies.…”
Section: Resultsmentioning
confidence: 97%
“…For the index test domain, we consider the risk of bias high in one study [35], because the index test results were interpreted without blinding of the reference standard findings. Also, we consider the risk of bias unclear in another four studies [24, 29, 32, 33], because we were unable to confirm whether the index test results were interpreted in a blinded manner of the reference standard findings. For the reference standard domain, we consider the risk of bias high in one study [35], because the reference standard findings were interpreted without blinding of the index test results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[34,36] Razek et al (2015) assessed the pattern of articular disc displacement in patients with internal derangement using US and concluded that the diagnostic efficacy of US for anterior displacement has sensitivity of 79.3%, specificity of 72.7%. [37] Other applications of US Periapical and intraosseous lesions, maxillofacial trauma, detection of foreign bodies, US guided fine needle biopsy, submandibular gland injection of botulinum toxin for hypersalivation in cerebral palsy and in basket retrieval of salivary stones. [11] US has gained an importance for squamous cell carcinoma (SCC) involving the base of the tongue which is difficult to assess clinically.…”
Section: Tmdsmentioning
confidence: 99%